Pengaruh Motivasi Ekstrinsik dan Intrinsik terhadap Kepuasan Kerja: Peran Kepemimpinan Transaksional di PT MAS Arya Semarang - Shania Krishna; Ardian Adhiatma (ARZUSIN, 2026)
Job satisfaction is an important factor in supporting employee productivity in manufacturing companies that implement target-oriented work systems. In the context of PT MAS Arya Semarang, a balance among extrinsic motivation, intrinsic motivation, and transactional leadership is required to improve employee job satisfaction. This study aimed to analyze the effects of extrinsic and intrinsic motivation on job satisfaction, both directly and through transactional leadership as a mediating variable. The study employed a quantitative approach, with data collected through questionnaires administered to employees of PT MAS Arya Semarang. The data were analyzed using the Partial Least Squares (PLS) method. The results showed that extrinsic motivation had a positive and significant effect on transactional leadership and job satisfaction. Intrinsic motivation had a negative and significant effect on transactional leadership but a positive and significant effect on job satisfaction. Transactional leadership also had a positive and significant effect on job satisfaction and was proven to mediate the effects of extrinsic and intrinsic motivation on job satisfaction. These findings confirm that improving employee job satisfaction requires the appropriate management of extrinsic and intrinsic motivation and the effective implementation of transactional leadership. The practical implications of this study indicate that the company needs to integrate reward policies, strengthen internal motivation, and implement achievement-based leadership mechanisms to support improvements in productivity and company performance.